Konsep Toleransi Beragama dalam al-Qur’an dan Weda: Analisis Komparatif atas Prinsip Perdamaian, Pluralitas, Musyawarah dan Keadilan - Alven Putra; Aan Andesra; Zakiyah; M Alfin Al Muzaki (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study examines the concept of religious tolerance in the Qur’an and the Vedas. The objective of this research is to explore abd compare the concepts of religious tolerance presented ih these two sacred scriptures by analyzing several key, aspects, namely the principles of peace, plurality, deliberation (consultation), and justice. This research employs a qualitative approach using a library research method. The primary data consist of verses from the Qur’an and the Vedas related to religious tolerance within the predetermined aspects of peace, plurality, deliberation, and justice. Secondary data are obtained from relevan books, scholarly journals, and academic articles. The data are analysed using a descriptive-ana;ytical method, which aims to provide a systematic description and explanation of specific facts and concepts. This approach enables a comaparative analysis of the perspectives of the Qur’an and the Vedas on religious tolerance. The findings reveal that both the Qur’an and the Vedas contain numerous passages encouraging tolerance toward followers of other religions, particularly in matters of social interaction, with the aim of fostering harmonious and peaceful coexistence. However, both scriptures draw clear boundaries regarding tolerance in matters of faith (aqidah) and religious worship, where compromise is not permitted. Outside these domains, tolerance is encouraged and considered acceptable. This study contributes to a deeper understanding of religious tolerance from the perspectives of the Qur’an and the Vedas and provides valuable insight for future research in religious studies and the study of tolerance within multicultural societies.